Determining the Phosphorus Release for Natuphos E 5,000 G Phytase for Nursery Pigs - K. M. Gourley; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 286 nursery pigs (PIC 327 × 1050; initially 24.3 lb and d 42 of age) were used in a 21-d growth trial to determine the available P (aP) release curve for a novel phytase source (Natuphos E 5,000 G, BASF Corporation, Florham Park, NJ). Pigs were randomly allotted to pens at weaning. On d 0 of the experiment (d 18 after weaning), pens were allotted in a randomized complete block design to 1 of 8 treatments. There were 4 pigs per pen and 9 pens per treatment. Pigs were fed a corn-soybean meal-based diet formulated to 1.25% standardized ileal digestible (SID) lysine. Ten 1-ton batches of basal feed (0.12% aP) were manufactured and subsequently divided to be the major portion of experimental diet manufacturing. Experimental diets were formulated to contain increasing aP supplied by either an inorganic source (0.12, 0.18, and 0.24% aP from monocalcium P) or from increased phytase (150, 250, 500, 750, and 1,000 FTU/ kg). Diets were analyzed for phytase using the AOAC method and actual analyzed concentrations were 263, 397, 618, 1,100, and 1,350 FTU/kg, respectively. On d 21 of the study, one pig per pen was euthanized and the right fibula was collected for bone ash and percentage bone ash calculations. From d 0 to 21, increasing P from inorganic P or increasing phytase resulted in improved (linear, P<0.01) ADG, F/G and ending BW. Bone ash weight and percentage bone ash increased (linear, P<0.01) with increasing inorganic P or phytase. When formulated phytase values and percentage bone ash are used as the response variables, aP release for up to 1,000 FTU/kg of Natuphos E 5,000 G phytase can be predicted by the equation: aP release = 0.000212 × FTU/kg phytase.
Keywords: bone ash; nursery pigs; phosphorus; phytase